A PTPN11 mutation in a woman with Noonan syndrome and protein-losing enteropathy - Wang, Na (BMC Gastroenterol, 2020)
BACKGROUND: Noonan syndrome is an autosomal dominant, variably expressed multisystem disorder characterized by specific facial and cardiac defects, delayed growth, ectodermal abnormalities, and lymphatic dysplasias. Lymphedema and chylous pleural effusions are common in Noonan syndrome, but protein-losing enteropathy (PLE) has only rarely been described in the condition and little is known about its genetic associations. CASE PRESENTATION: We report the case of a 30-year-old Chinese woman who developed severe recurrent edema and hypoproteinemia. Gastroduodenoscopy showed a “snowflake” appearance of lymphangiectasia in the duodenum, and CT reconstruction of the small intestine showed segmental thickening of the intestinal wall with localized stenosis. Whole exome sequencing revealed that the patient harbored a pathogenic variant of PTPN11 (c.A922G p.N308D), which was unfortunately inherited by her 2.5-year-old daughter who had short stature and atrial septal defect but no hypoproteinemia. CONCLUSIONS: This case of Noonan syndrome with PLE was associated with a PTPN11 mutation. A comprehensive review of PLE in Noonan syndrome revealed that PLE often presents late in this context but there is no clear genotype-phenotype correlation. Genetic evaluation with next-generation sequencing can be useful for securing the diagnosis and planning early intervention and management.